What made Britannia great? Did the Industrial Revolution make Britain a world power? - Gregory Clark (University of California, Department of Economics, 2006)
How much of Britain's high living standards and military power compared to its competitors in 1850 should be attributed to Britain having first experienced the Industrial Revolution? Examining data on real wages in the north and south of England, the Netherlands and Ireland in the Industrial Revolution era, this paper contends that most of the technological advances of the Industrial Revolution benefited Britain's competitors as much as Britain itself. Britain attained higher outputs per person and higher living standards before the Industrial Revolution, not because of it. Her growing military power and industrial might in the years 1740 to 1850 was instead the product of its unusually rapid population growth. Britain's rise to world dominance was a product more of the bedroom labors of British workers than of their factory toil.
Keywords: 330